The relationship between macroeconomic variables and economic growth: evidence from ASEAN countries / Nafisah Ahmad - Ahmad, Nafisah (2018)
It is crucial to pay attention to the level of the economy of a country. This is because it will affect the life of people. Economic gowth plays a vital role to preserve the prosperity of the citizen. Gross domestic product is a standard measure that being used to monitor the growth. Macroeconomic variables help to increase and improve the economy of a region. The macroeconomic variables used by the researcher in this study are export, import, foreign direct investment, inflation and interest rate. The main purpose of this research is to investigate the relationship between each macroeconomic variable and economic growth in the major ASEAN countries (Malaysia, Indonesia, Singapore, Thailand, Vietnam, Philippine and Myanmar). The researcher applies econometric technique of panel ordinary least square to find the link between the variables and economic growth. The analysis that has been carried out are descriptive, correlation, regression and normality test. Based on the correlation, the researcher found that export, import and FDI have weak positive relationship with economic growth. Inflation and interest rate has weak negative correlation with economic growth. In regression analysis, import, FDI, inflation and interest rate have significant relationship with economic growth, while export does not have relationship with dependent variable. The model regression is fit because it has probability that less than 5%. Normality test also found that the data is normally distributed as it has failed to reject the null hypothesis.